2014
DOI: 10.7883/yoken.67.356
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Group B Streptococcus Isolated from Infants with Invasive Infections: A Population-Based Study in Japan

Abstract: SUMMARY: Group B Streptococcus (GBS) is one of the leading causes of neonatal bacterial infections. Population-based surveillance of GBS-related invasive diseases among newborns and infants from 10 prefectures in Japan was performed between 2007 and 2012. The characteristics of cases and isolated GBS are described in this study. The incidence rate of GBS-related invasive diseases was 0.13 per 1,000 live births. Analysis of GBS samples obtained from 60 invasive cases showed that the most frequent serotypes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
1
18
2
Order By: Relevance
“…The overall incidence of invasive neonatal GBS disease (0.55 per 1000 live births, 95% CI 0.44–0.69) in Guangdong between 2011 and 2014, was close to the global average estimation (0.53 per 1000 live births, 95% CI 0.44–0.62) [ 5 ]. However the incidence rate in this study is much higher than which was suggested in our previous short-term observation [ 10 ] and in other Asian countries with the incidences rate 0.14–0.41 per 1000 live births [ 12 , 13 ]. Furthermore, GBS in EOD increased markedly from 2011 to 2014, reaching 0.58 per 1000 live births.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The overall incidence of invasive neonatal GBS disease (0.55 per 1000 live births, 95% CI 0.44–0.69) in Guangdong between 2011 and 2014, was close to the global average estimation (0.53 per 1000 live births, 95% CI 0.44–0.62) [ 5 ]. However the incidence rate in this study is much higher than which was suggested in our previous short-term observation [ 10 ] and in other Asian countries with the incidences rate 0.14–0.41 per 1000 live births [ 12 , 13 ]. Furthermore, GBS in EOD increased markedly from 2011 to 2014, reaching 0.58 per 1000 live births.…”
Section: Discussioncontrasting
confidence: 71%
“…In this study the proportion of EOD (70%) is higher than that of LOD (30%). In other Asian countries such as Japan and Korea, reported that the LOD account for 75% (45/60) and 80% (125/157), respectively [ 13 , 15 ]. An important risk factor for EOD is GBS colonization of maternal vaginal and rectal sites during late pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated a pooled 39% (95%CI:25–53) of maternal colonisation isolates as serotypes VI-IX (from 5 studies, n = 728 isolates) [62] , [71] , [72] , [73] , [74] . However, we found these serotypes to be less frequently reported as causing invasive disease in infants, with 8% (95%CI:2–15) of EOGBS (4studies) [75] , [76] , [77] , [78] , and 1% (95%CI:0–3) of LOGBS (3studies) [75] , [77] , [78] , while serotype III still predominates in these cases with 38% (95%CI:26–51) in EOGBS and 36% (95%CI:3–79) in LOGBS. Protein vaccines could theoretically reduce the risk of serotype replacement that theoretically exists for GBS capsular-polysaccharide based vaccines.…”
Section: Discussionmentioning
confidence: 71%
“…The high specificity of Real-LAMP relied on well-designed primers, which ensured strict alignment between primers and targeted region, not only facilitating major amplification of the targeted sequence but also differentiating one-base pair-difference among all similar templates; to avoid any interference with non-targeted DNA sequences [6]. In the present study, LAMP was performed to detect the presence of DNA samples for Sa and 10 other strains of common pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%